Joan Heath interviews Suzanne Cory and Joan Steitz: a female perspective of science in the swinging ‘60s - Joan Heath; Suzanne Cory; Joan Steitz (Disease Models & Mechanisms, 2022)
Prompted by the occasion of International Women's Day, Joan Heath and DMM reunited Professors Suzanne Cory and Joan Steitz via Zoom to discuss their extraordinary careers and joint experiences in science. They also delve into past and present challenges for women in science, and discuss the role of scientists in a post-pandemic world.